The good luck book : a celebration of global traditions, superstitions, and folklore - Alexander, Heather, 1967- (DK Publishing, 2023)
"Ever wonder why we...knock on wood, blow out candles on a cake, or cross our fingers for good luck? Discover superstitions old and new from around the world, learn about how they started, and which ones are still popular."--